The Problem of Normative Inconsistency in Legislation in Indonesia: An Analysis from the Perspective of Legal Science - Kaharudin, Kaharudin; Wiratama, Muhammad Naufal; Ali, Mochamad Daffa Khaedar; Wijaksono, Aris (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Normative inconsistency within Indonesia’s legal regulatory system continues to be a significant challenge that disrupts legal certainty, weakens policy implementation, and complicates coordination among government bodies. This study examines the various manifestations of inconsistent norms, explores the root causes behind these discrepancies, and presents solutions based on legislative drafting theory. Using a normative juridical approach, the research relies on extensive literature review of laws, regulations, and academic sources relevant to the topic. The results indicate that inconsistencies appear in several forms, such as overlapping authority between central and regional governments, a mismatch between legal provisions and on-the-ground implementation, unequal funding distribution, insufficient oversight, and inconsistent law enforcement. Contributing factors include inadequate regulatory harmonization, limited expertise among legal drafters, restricted public involvement, political and economic interests, and the proliferation of excessive regulations. From a legislative drafting perspective, addressing these problems requires strict adherence to foundational lawmaking principles, improved harmonization methods, enhanced capacity-building for regulatory drafters, and institutionalized post-legislative review. This study concludes that systematic regulation planning, integrated harmonization, and continuous evaluation are crucial to achieving a coherent and equitable national legal framework.